Pengaruh Implementasi Projek Majalah Dinding Terhadap Peningkatan Karakter Nalar Kritis Siswa Sekolah Dasar - Dwi Permana, Rangga (Jurnal Didaktika Pendidikan Dasar, 2025)
Based on data from the academic report cards of SDN Pondok Bambu 06 in 2024, it was found that students’ critical thinking skills need to be improved the most. The Pancasila Student Profile Strengthening Project is one of the solutions to this problem. The chosen project is to create a wall magazine from used goods. This study aims to find out the influence of implementing the wall magazine project on students’ critical thinking skills. The research approach used is quantitative with a correlational or associative research method that aims to find the influence of the independent variable on the dependent variable. The sample used was 30 students of class 5 A using purposive sampling with judgment sampling type. The data was obtained from the results of the assessment using the wall magazine implementation rubric and the critical thinking ability rubric. The magnitude of the coefficient of determination, 0.4014, provides an overview that the improvement of critical thinking is influenced by the implementation of the wall magazine project by 40.14%. tcount 4.521511 and ttable 1.701131 with a p-value of 0.000102 < 0.05 illustrates that the implementation of the wall magazine project has a significant effect on improving students’ critical thinking character.